Abraham Lincoln, vampire hunter [videorecording (DVD)] - Bekmambetov, Timur, 1961-; Walker, Benjamin, 1982-; Cooper, Dominic, 1978-; Mackie, Anthony, 1978-; Sewell, Rufus, 1967-; Winstead, Mary Elizabeth; Burton, Tim, 1958- (20th Century Fox Home Entertainment, 2012)
Abraham Lincoln, history's greatest hunter of the undead, must risk the presidency, his family, and his life to protect America from the bloodthirsty vampires.